Tożsamość wirtualna a relacje międzykulturowe .......... 443 - Kosyna, Karolina (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
VIRTUAL IDENTITY AND INTERCULTURAL RELATIONS: AN ANTHROPOLOGICAL PERSPECTIVE ON DIGITAL INTERACTIONSIn the era of globalization and increasing digitalization, virtual spaces have become hubs for intensive intercultural interactions. This article offers an anthropological analysis of virtual identity, exploring how users from different cultures shape and negotiate their identities in digital environments. It examines issues related to bonding, the emergence of new transcultural communities, and the challenges traditional cultural norms face in the rapidly evolving online landscape. Special attention is given to phenomena such as meme culture, translocality in online gaming, and the use of social media as a platform for intercultural dialogue.